Correction: Catalyst: Fast and flexible modeling of reaction networks. - Torkel E Loman; Yingbo Ma; Vasily Ilin; Shashi Gowda; Niklas Korsbo; Nikhil Yewale; Chris Rackauckas; Samuel A Isaacson (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1011530.].